A review on lithium combustion. (15th January 2016) - Schiemann, Martin; Bergthorson, Jeffrey; Fischer, Peter; Scherer, Viktor; Taroata, Dan; Schmid, Günther
Graphical abstract: Highlights: Lithium has the potential to act as energy fuel. Combustion techniques comparable to oil spray or pulverized coal combustion seem promising. Carbon free or carbon reducing processes are possible. Experimental and numerical results on lithium particle combustion already highlight the technical feasibility. Abstract: Lithium combustion has been studied for several decades, with a primary focus on safety issues, such as lithium fires resulting from spills in nuclear reactors. Several studies have also considered the use of lithium as a fuel within propellants, or within propulsion systems that burn lithium in the atmospheric "air" of other planets. Lithium safety has typically been investigated through combustion of molten pieces of lithium or within pool fires. For propulsion applications, experiments were carried out using packed beds of lithium particles. A novel approach that has recently been proposed is the use of lithium as a recyclable fuel, or energy carrier that can compactly store renewable energy. In this scheme, lithium is burned with air, or power-plant exhaust, to generate heat for thermal power systems when power is needed. The solid-phase combustion products would be collected and recycled, via electrolysis, back into elemental lithium when excess renewable power is available. This paper summarizes the existing knowledge on lithium combustion. It presents the available findings on lithium combustion for large single pieces of lithium, on pool fires, reaction in packed beds, as well as the combustion of sub-mm sized particles and droplets which are needed for the use of lithium as an energy carrier. The combustion reactions of lithium with O2, H2 O, CO2 and N2 are discussed. Modelling of lithium-particle combustion is at the early stages of development and available results are discussed.